Educating for Business, Public Service and the Social Sciences A History of the Faculty of Economics at the University of Sydney 1920-1999. - Groenewegen, Peter (Sydney University Press, 2009)
Tertiary economics and business education started early in Australia but was not organised on a faculty basis until the 20th century. Commerce and business teaching at Sydney University began in 1906, and from 1920 was taught in the Faculty of Economics, together with public administration and accounting. Its progress for the next 80 years is chronicled in this comprehensive history of the Faculty of Economics.